System productivity and economics as influenced by cropping system and nutrient management - MEENA, S L; BANA, R S; SEPAT, SEEMA; DASS, ANCHAL (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during kharif, rabi and summer 2013-16 at ICAR-IARI, New Delhi to study the effect of cropping systems and nutrient management on productivity of different crops and cropping systems, the impact of nutrient management on nutrient uptake in different crops and cropping systems and to evaluate economics of different cropping systems. Experiments were conducted in split-plot design replicated thrice. The treatments were comprised five cropping systems, i.e. pearl millet-wheat, pearl millet-mustard-cowpea, pearl millet-wheat-bottle gourd, clusterbean-mustard-cowpea, and clusterbean-wheat-bottle gourd and four nutrient management, i.e. control, RDN (recommended dose of nitrogen), 50% RDN + 50% N through FYM, and 50% RDN + 50% N through FYM + biofertilizers. All the recommended practices except treatment were adopted. The soil test value based nutrient application was done. Results revealed that maximum pearl millet equivalent yield (13.8 t/ha), production efficiency (37.8 kg/ha/day), rainfall-use efficiency (4.34 kg/ha-mm), net returns (â‚¹89198) and benefit cost ratio (2.55) were found under the cropping system of pearl millet-mustard-cowpea. Total nitrogen uptake was obtained more under pearl millet-wheat-bottle gourd. The nutrient management practice of RDN gave higher pearl millet equivalent yield (13.5 t/ha), production efficiency (37 kg/ha/day), rainfall-use efficiency (4.25 kg/ha-mm), total N uptake (120.2 kg/ ha) and net returns (â‚¹ 80243) but statistically at par with 50% RDN + 50% N-FYM + BF. The highest benefit cost ratio was recorded in 50% RDN + 50% N-FYM + BF (2.07). It is concluded that the cropping system of pearl milletmustard- cowpea with nutrient management practice of 50% RDN + 50% N-FYM + BF produced significantly higher yields and income.